Emotions as ways of engaging the world. The case of anger - López Carrascal, Luisa Fernanda (Estudios de Filosofía, 2016)
This article highlights the moral dimension of emotions, particularly anger, from the cognitive-evaluative perspective proposed by Martha Nussbaum and Robert Solomon. This standpoint faces the stoic position that emotions are destructive and irrational. The contribution of Aristotle is essential in the argumentation of this article. It considers especially Aristotle’s proposal that the emotions are appropriate or not, rather than rational or irrational.